The Impact of Participating in a Juvenile Offender Mentorship Course on Students' Perceptions of the Legal System and Juvenile Offenders. Issue 4 (1st October 2020) - Pica, Emily; Fripp, Jessica A.
Abstract: The current study examined how a mentorship course, whereby students work with juvenile offenders, influenced their perceptions of the legal system and juvenile offenders. Undergraduate students ( N  = 13) enrolled in a course centered around mentoring juvenile offenders. Students attended lecture to learn the theoretical and conceptual background of juvenile justice and juvenile offenders. Additionally, students were expected to meet with their mentee, a juvenile offender, once a week. Measures concerning attitudes toward juvenile offenders were given the first day of class and again on the last day of class. Overall, attitudes were shown to change from pre- to post-testing; specifically, attitudes toward juvenile offenders were significantly more positive at post-test. As demonstrated in this study, both in-class material and hands on application of course material can influence student attitudes toward a given population and also encourages them to engage in higher order levels of thinking.